THE DIPLOMATIC ACTIVITIES OF ALEXANDER THE GREAT IN THE ROLE OF CULTURAL RAPPROCHEMENT BETWEEN THE WEST AND THE EAST (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
The article highlights that Alexander created the public opinion he needed through diplomatic means; used the struggle of various party groups to achieve his goal; separated the forces and opposition that rebelled against him. He also demonstrated his diplomatic skill in political and religious demonstrations; in diplomatic games both with one’s own army and with the conquered population; in pursuing a subtle policy of relations with defeated countries and peoples.